Secure communication and image encryption scheme based on synchronisation of fractional order chaotic systems using backstepping. (2018) - Shukla, M.K.; Sharma, B.B.
Synchronisation strategy of fractional order nonlinear dynamical systems is utilised to address the problem of secure communication by introducing additional security features. Initially, a backstepping-based controller is designed for synchronisation of two similar fractional order chaotic systems in master-slave configuration. The controller obtained is divided into two parts with one part transmitted through the communication channel whereas the other part has to be designed at the receiver end so as to obtain synchronisation between master and slave system. Further, only two signals are transmitted out of which one has an embedded message signal and the other is a complex combination of master states which will be used for synchronisation purpose at the receiver end for recovery of message signal. The initial conditions, system parameters, fractional orders, the structure of controller and the combination of master system states form a large key set which should be known is advance in order to breach the security. Here, the scheme for secure transmission of speech signal is presented first and further a scheme for image encryption is given. The simulation results and security analysis using different quantitative measures are presented at the end to demonstrate the applicability and effectiveness of the proposed scheme.